PENGARUH PERPUTARAN KAS, PERPUTARAN PERSEDIAAN DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR PERIODE PASCA COVID TAHUN 2021-2022 - Putri, Ane; Novatania, Elsa; Putra, M. Shama; Tanno, Aries (Jurnal Akuntansi Kompetif, 2024)
This study aims to examine the effect of cash turnover, inventory turnover and accounts receivable turnover on the profitability of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. This study wants to find out how the company's profitability after covid-19. The research population is all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period after covid-19, namely 2021 and 2022. The sample used is all companies that earn profits. The sampling method uses purposive sampling method. This study uses multiple linear regression analysis tools with the SPSS version 23 program to test the hypothesis. The results showed that simultaneously all variables affect the profitability of the company. Partially, only accounts receivable turnover has a significant effect, while cash turnover and inventory turnover have no effect on company profitability.